Verify that x^3+y^3+z^3-3xyz=1/2(x+y+z)[(x-y) ^+( y- z) ^ +(z-x) ^]
Answers
Answered by
19
Answer:
First We take R.H.S & use the Formula [( a-b)²= a²+b²-2ab] & simplify it then R.H.S becomes equal to L.H.S
R.H.S
⇒ 1/2×(x + y + z) (x²+ y²-2xy +y²+ z²-2yz+x²+z²-2xz)
[( a-b)²= a²+b²-2ab]
⇒ 1/2×(x + y + z) (2x²+ 2y²+2z²-2xy -2yz-2xz)
⇒ 1/2×(x + y + z) 2(x² + y²+ z² – xy – yz – xz)
=(x + y + z) (x² + y²+ z² – xy – yz – xz)
= x³+y³+z³-3xyz
= L.H.S
We know that,
[x³+ y³ + z³– 3xyz = (x + y + z)(x²+ y² + z² – xy – yz – xz)]
L.H.S = R.H.S
[x³+ y³ + z³– 3xyz = (x + y + z)(x²+ y² + z² – xy – yz – xz)]
Step-by-step explanation:
please mark my answer brainlists and follow i will follow you
Answered by
15
PLZ MARK AS BRAINLIEST..
Hope it hlps u...
❤❤❤❤✌
Attachments:
![](https://hi-static.z-dn.net/files/dd0/93edcf085da56078fac21b27a75d94b3.jpg)
Similar questions